Depletion of Small HDL Subclasses Predicts Poor Survival in Liver Cirrhosis - Anja Pammer; Tobias Madl; Hansjörg Habisch; Jakob Kerbl-Knapp; Florian Rainer; Vanessa Stadlbauer; Angela Horvath; Philipp Douschan; Rudolf E. Stauber; Gunther Marsche (Antioxidants)
Liver cirrhosis is a complex condition characterized by oxidative stress, inflammation, and metabolic dysfunction, contributing to systemic complications and high mortality. High-density lipoprotein (HDL), particularly its small subclasses, is known for its antioxidant, anti-inflammatory, and cholesterol efflux capacities. This study examined changes in HDL subclass distribution and composition in cirrhosis and assessed their prognostic relevance for mortality. We analyzed HDL profiles using nuclear magnetic resonance spectroscopy in patients with compensated (n = 205) and decompensated (n = 158) cirrhosis, compared to healthy controls (n = 16). Across all HDL subclasses in cirrhotic patients, cholesterol content was decreased, and triglyceride levels were elevated. In particular, compensated cirrhosis was associated with a marked reduction in small and extra-small HDL particles, while large HDL levels remained unchanged. This reduction was even more pronounced in decompensated disease. Small HDL particle levels were inversely correlated with oxidative stress markers and liver dysfunction and independently predicted 12-month mortality in patients with compensated cirrhosis, even after adjusting for MELD score. In conclusion, our findings highlight a substantial depletion of small and extra-small HDL particles as a key feature of cirrhosis, linked to oxidative stress and mortality in the compensated stage.